TAX AVOIDANCE: AGENCY AND CONTINGENCY PERSPECTIVES ON KEY FINANCIAL DRIVERS - Paulus, Hendro; Awaludin, Awaludin; Ciptaningtyas, Metta; Siagian, Nancy Neorita (Unversitas Prof. Dr. Moestopo (Beragama), 2026)
This study investigates the effect of profitability (ROA), leverage (DER), and asset efficiency (TATO) on tax avoidance (TA), with sales growth (SG) as a moderating variable. Using 140 panel data observations from transportation companies listed on the Indonesia Stock Exchange for 2020–2024, the analysis was conducted using EViews 13. The results show that ROA and DER positively and significantly influence tax avoidance, while TATO has no significant effect. Sales growth strengthens the relationship between ROA and tax avoidance and between DER and tax avoidance, but does not moderate the effect of TATO. These findings support Agency Theory, indicating that financial pressures encourage managerial tax-minimizing behavior, and align with Contingency Theory, showing that contextual factors such as sales growth shape corporate tax strategies. This study provides empirical insights for regulators and stakeholders in identifying firms with higher tax avoidance tendencies